Intertemporal Dynamics of Sustainability Disclosures: Evidence of Contemporaneous and Lagged Performance Effects in Indian Firms - Shandilya, Adrija; Banik, Gour Gopal (Indonesian Journal of Sustainability Accounting and Management, 2026)
The paper investigates the linkage between corporate sustainability policies and the firm performance of companies listed on the NIFTY 50 index, over the post-BRSR period (2021-22 to 2024-25). Going beyond aggregate measures, the research uses a disaggregated approach by analyzing environmental, social, and economic dimensions individually, along with a general measure of sustainability. Furthermore, a one-year lagged framework is included to reflect delays in the outcomes of sustainability investments on financial performance. The pooled Ordinary Least Squares (OLS) regression is used to construct and analyze a near-balanced panel dataset supported by descriptive statistics and correlation analysis. Return on Assets (ROA) and Return on Equity (ROE) are used to measure firm performance, with firm size serving as a control variable. The results suggest the existence of a differentiated association of sustainability practices with the measures and dimensions of performance. The overall sustainability construct demonstrates a stronger association with operational performance (ROA) relative to individual dimensions, whereas no significant relationship is observed with shareholder returns (ROE). Moreover, the one-year lagged analysis indicates that sustainability practices are associated with effects that may be realized over time rather than immediately. The research contributes to the body of literature on sustainable development and performance identification by jointly analyzing both dimension-specific and aggregate impacts within a one-year lag framework. Using post-BRSR Indian firm-level data, it uncovers differential and intertemporal impacts of sustainability practices, highlighting their stronger influence on operational efficiency than on immediate shareholder returns.